2017
DOI: 10.26420/austinjgastroenterol.2017.1082
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Markers of Inflammatory Bowel Disease: Past, Present, and Future

Abstract: Ulcerative colitis (UC) and Crohn's disease (CD) exemplify the two main arms of the spectrum of an idiopathic chronic disease known as inflammatory bowel disease (IBD). To date, this disease remained a puzzling dilemma in many aspects; including difficulties in its etiology/pathogenesis, diagnosis, severity assessment, treatment and outcomes/complications. Physicians usually get the diagnosis of IBD through a combination of clinical features, laboratory tests, radiology, as well as the invasive technique of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…provides information about the cellular immune system activation [53][54][55][56]58] for the purpose of diagnosis, successful treatment and prognosis of inflammatory states, including atherosclerosis [56,59,60], malignancies (cancer and leukemia) [61], vascular (cardiovascular-, brain vascular, peripheral artery vascular) [59,62,63], neurological, autoimmune, and many other socially important diseases [e.g. acquired immune deficiency syndrome (AIDS); other viral and bacterial infections], aging-related disorders, including MS [56,57,60,[64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…provides information about the cellular immune system activation [53][54][55][56]58] for the purpose of diagnosis, successful treatment and prognosis of inflammatory states, including atherosclerosis [56,59,60], malignancies (cancer and leukemia) [61], vascular (cardiovascular-, brain vascular, peripheral artery vascular) [59,62,63], neurological, autoimmune, and many other socially important diseases [e.g. acquired immune deficiency syndrome (AIDS); other viral and bacterial infections], aging-related disorders, including MS [56,57,60,[64][65][66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…The MPO level in a stool examination has been proved as a noninvasive biomarker for response to treatment in patients with CD and UC [ 70 ]. Studies have shown that a high concentration of MPO after treatment suggests an incomplete response to the treatment [ 73 ].…”
Section: The Upcoming Fecal Inflammatory Markersmentioning
confidence: 99%
“…Increased M2-PK stool level was also found in pediatric patients with active CD compared to control patients. Pyruvate kinase is a promising sensitive screening tool for intestinal inflammation and its severity indicator [ 73 , 74 ].…”
Section: The Upcoming Fecal Inflammatory Markersmentioning
confidence: 99%
See 2 more Smart Citations